Student Perspectives on the Use of AI Tools in Conducting Research Project at BS Level - Ms. Iram Naz; Dr. Misbah Malik; Dr. Muhammad Irfan (Policy Journal of Social Science Review, 2026)
This study aimed to investigate the attitudes and perceptions of the BS students regarding the use of Artificial Intelligence (AI) tools in their research project processes. This study sought to investigate students' perceptions of AI tools, understand the benefits and obstacles students face in using these tools in the research process, and gauge students' opinions on the ethical implications of AI use in academic research. A qualitative phenomenological approach was employed within the constructivist paradigm to gain an in-depth understanding of students' lived experiences. Semi-structured interviews were conducted with 10 BS students who were selected by purposive sampling. Thematic Analysis was used to analyze the interview data. Students' Perspectives on the Use of AI Tools in Research Projects, Benefits and Challenges of Using AI Tools During the Research Process, and Impact and Ethical Considerations of AI Tools in Research emerged as the three main themes derived from the findings. The findings showed that the students generally felt that AI tools are useful academic assistants that can enhance the efficiency of research, academic writing, literature review, and learning. However, there were some concerns raised, including the presence of misinformation, fabricated references, plagiarism, and the use of AI-generated content. Students highlighted the need to check facts created by AI, to ensure academic honesty, and to use AI responsibly. The researchers conclude that AI can be a beneficial tool to support undergraduate research ethically and critically. It suggests that universities establish explicit policies regarding AI, implement AI literacy programs, and advocate responsible and ethical use of AI tools to harness their educational potential while upholding academic integrity. Keywords: Artificial Intelligence (AI), AI Tools, Student Perspectives, Research Projects, Qualitative Research, Thematic Analysis, Academic Integrity, Higher Education.